MENGEMBANGKAN PENDIDIKAN BERWAWASAN KEUMMATAN - Rosniati Hakim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This paper discusses the possibilities that Islamic Education needs life system as stated in the Holy Koran. This life system must consist of moral as the central theme. The method used in this study was discourse analysis. The term “ummah” which is social study is known as “kemasyarakatan (social life)” was analyzed through Islamic education so that it results in education conception with social conception. It consists of the issue that every educator needs at least three requirements that must be fulfilled in order to prepare learners to be able to achieve the position as the best people (khairu ummah): amar makruf, nahi munkar, and commitment to be loyal to Allah‟s rules. The objective of the education expected to get the guidance, victory (falah), and save from the torments. The method used was through providing evidences/ arguments, stories, wisdom, mau‟izhah, mujadilah, syufa and ishlah. The educator is the role model in the field and action. Learners are the best people as individual and group.